Long-Term Effects of Iron Chelating Agents on Ocular Function in Patients with Thalassemia Major - Nuzzi R (Dove Medical Press, 2021)
Raffaele Nuzzi,1 Giada Geronazzo,1,2 Federico Tridico,1 Alessia Nuzzi,3 Paolo Caselgrandi,1 Antonio Giulio Piga4 1Eye Clinic Section, Department of Surgical Sciences, University of Turin, Turin, Italy; 2Regional Reference Centre for Diagnosis and Cure of Hemoglobinopathies, S. Luigi Gonzaga University Hospital, University of Turin, Orbassano (TO), Italy; 3Department of Clinical Sciences and Community Health, Eye Clinic San Giuseppe Hospital, IRCCS Multimedica, University of Milan, Milan, Italy; 4Head of Regional Reference Centre for Diagnosis and Cure of Hemoglobinopathies, S. Luigi Gonzaga University Hospital, University of Turin, Orbassano (TO), ItalyCorrespondence: Raffaele NuzziEye Clinic Section, Department of Surgical Sciences, University of Turin, Via Cherasco 23, Turin, 10126, ItalyEmail prof.nuzzi_raffaele@hotmail.itBackground: The aim of this study is to evaluate eye structures and function in patients receiving iron chelating therapy and to assess whether a correlation exists between the onset of ocular alterations and the intake of iron chelating drugs.Methods: A prospective cohort study was performed. Eighty-eight patients, composed of children and adults with thalassemia major (TM) who are taking or had taken iron chelating drugs (deferoxamine, deferiprone or deferasirox), have been initially enrolled in the study. The final sample featured 80 patients, including 18 children and 62 adults. These subjects received an eye examination to evaluate intraocular pressure (IOP), best corrected visual acuity (BCVA), the presence of refractive defects, cornea, anterior chamber, lens, fundus oculi, visual field and mean retinal nerve fiber layer (RNFL) thickness. Logistic regression model analysis was performed in order to assess any correlation. In addition, a literature search regarding the relation between iron chelating drugs and ocular adverse events was carried out to compare the results obtained with the evidence in the literature.Results: Logistic regression did not report a significant correlation between the intake of iron chelating drugs and the onset of anterior ocular segment alterations, lens opacities, retinal diseases, optical neuropathies, astigmatism, visual field and RNFL thickness defects. Logistic regression returned a statistically significant correlation between myopia and iron chelation therapy (p-value 0.04; OR 1.05) and also between presbyopia and total duration of therapy with deferoxamine (p-value 0.03; OR 1.21). Although intraocular pressure levels remained within the normal range, a significant correlation with the length of deferoxamine therapy has been found (p-value 0.002; association coefficient − 0.12). A negative correlation between deferiprone and presbyopia has also been observed.Conclusion: Iron chelation therapy is not associated with severe visual function alterations. Limitation of deferoxamine treatment can help prevent ocular complications. Deferiprone and/or deferasirox may be preferable, especially in patients over age 40 years.Keywords: iron chelation, ocular adverse effects, deferiprone, deferasirox, deferoxamine